Much Ado about Nothing?- The Influence of Functional Food on Profitability of German Food Industry. - Antje Wittkopp (Kiel University, Department of Food Economics and Consumption Studies, 2002)
Product innovation is a competitive strategy in food industry. Successful product development management is a key determinant of a firm's performance. In recent years functional foods, which are innovative food products that provide health benefits beyond basic nutrition, have become increasingly important in Germany. Using the structure-conductperformance approach it can be argued that product innovation raises barriers to entry and thus improve profitability. This study examines the effect of functional food innovative activity (compared to overall innovative activity) on the profitability of 23 German food industry sectors from 1995 to 1999. Panel data analysis also includes concentration, firm size, market size and growth, advertising expenditure and capital intensity. While a positive relationship between product introduction and profitability was hypothesized, it is not supported by data.
Keywords: 330; product innovation; functional food; market structure; profitability; structureconduct-performance approach; food industry; panel data analysis; Gesundheitskost; Innovation; Nahrungsmittelgewerbe; Rentabilität; Schätzung; Deutschland